Ultra-long carbon nanotube-paraffin composites of record thermal conductivity and high phase change enthalpy among paraffin-based heat storage materials. (April 2021) - Kuziel, Anna W.; Dzido, Grzegorz; Turczyn, Roman; Jędrysiak, Rafał G.; Kolanowska, Anna; Tracz, Anna; Zięba, Wojciech; Cyganiuk, Aleksandra; Terzyk, Artur P.; Boncel, Sławomir
Highlights: Ultra-long carbon nanotube-paraffin composites are superior phase change materials. The composites are characterized by up to 161%-enhanced thermal conductivity. The composites display 6.3%-higher enthalpy of phase change as compared to paraffin. Supercooling of the composites at phase change is as low as 2.4 °C. Ordered nanotubes induce rapider nucleation via templating of paraffin crystallites. Abstract: Phase change materials (PCMs) are capable of storage considerably more energy than the conventional systems based on sensible heat. Despite immense and global research, there is a continuous pursuit for high-performance PCMs among which carbon nanocomposites emerge as the most prospective ones. In this paper, by comprehensive analysis of carbon nanotubes (CNTs) of three various morphologies (crystallinity, number of walls, and aspect ratio), we report record-breaking characteristics of CNT-paraffin nanocomposites based on ultra-long (770 μm) in-house multi-wall CNTs (MWCNTs) as fully functional PCMs prepared by a melting technique. By systematic investigations covering scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and analysis of thermophysical properties, we have constructed the most promising MWCNT(0.5% wt.)-paraffin nanocomposite of 37%-enhanced thermal conductivity and 6.3%-higher enthalpy of phase change ( ∆Hm ), in reference to the base paraffin, as well as excellent cycling stability (>50 heating/cooling cycles), and as low supercooling temperature ( ∆T=Tm – Tc ) as 2.4 °C. The superior characteristics derive from rapider nucleation of larger crystallites by MWCNTs proceeding via short- and long-range templating as well as intrinsic characteristics of individual and fibrous ultra-long MWCNTs. Additionally, even a 161%-enhancement in thermal conductivity is available for the long MWCNT-paraffin composite, but at the cost of preserving the remaining thermophysical characteristics of neat paraffin. The results clearly point out the potential of the elaborated PCMs toward thermal energy storage. Graphical abstract: Image, graphical abstract